Four Patterns of Abnormal Ring-Like Uptakes on Dedicated Breast PET. (26th August 2021) - Sasada, Shinsuke; Kai, Azusa; Kimura, Yuri; Masumoto, Norio; Kadoya, Takayuki
Abstract: The high resolution of dedicated breast PET (dbPET) enables the visualization of small breast cancers and a heterogeneity of breast tumors. Some tumors present with a ring-like appearance, the central uptake defect possibly reflecting intratumoral fibrosis and necrosis, associated with high-grade malignancy, and a triple-negative subtype. However, a ring-like finding is not only found in high-grade breast cancers. We describe 4 representative patterns of ring-like uptakes on dbPET: high-grade invasive cancer, intracystic tumor, extended noninvasive carcinoma, and change after vacuum-assisted breast biopsy. Ring-like uptakes on dbPET should be evaluated in association with clinical information.